Deskripsi Deskripsi Ecosemantik pada Karya Puisi D. Zamawi Imron - Ismatul Izzah; Anas Ahmadi; Budinuryanta Yohanes (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
Natural factors can encourage a work of poetry that taps humans' consciences so that they are aware of what they have done to the environment. The purpose of this study is to describe the basic study aspects of ontology from the work of D. Zamawi Imron, the axiology of cultural elements, and the linguistic epistemology contained in a poem produced. Qualitative research here also describes the results of the research, so it is not used to draw broader conclusions. In addition, comparative research is based on cause and effect or comparing something. The subject of this research is a poem by D. Zamawi Imron with an environmental or ecosemantic theme, which has been published in several books that can be downloaded on googlebookstore.com in 2022-2023. The results of the research from the semantic, ecosemantic, and ecological studies show a complex and layered representation of nature and its ecology, the integration of knowledge, and the analysis of the aspects of knowledge sources from the three elements of the poetry work of D. Zawawi Imron on its axiological, epistemological, and ecosemantic values.